FOODNET: information is changing things in the marketplace - Ferris, Shaun (Technical Centre for Agricultural and Rural Cooperation, 2004)
Shaun Ferris explains how FOODNET, an ASARECA marketing and agro-enterprise network for East and Central Africa, is delivering reliable market information to farmers in Uganda, using a mix of conventional media, the Internet, mobile phones and other ICTs